Legal Conflict In Marriage Registration: Between Compliance With Regulations And Practices In Society (Analysis Of Unregistered Marriage Cases Based On The Perspective Of Law No. 1 Of 1974 And The Compilation Of Islamic Law) - Firdaus, Muhammad Adhitya; Zuhdi Irfandi, Muhammad Sholeh; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Marriage is a sacred union desired by every married couple to build a household and have descendants. According to Article 2 paragraph 2 of Law Number 1 of 1974, a marriage is legally valid only when registered. This research analyzes the perspectives of Law Number 1 of 1974 and the Compilation of Islamic Law on unregistered marriages and their legal consequences using a library research and qualitative-statute approach.